Teaching Grammar in Intensive Program at Language Development Center - Pasaribu, Nursaadah; Harida, Eka Sustri; Sinaga, Yusni (English Education : English Journal for Teaching and Learning, 2023)
This study aims to find out what strategies used in teaching grammar. This research used descriptive qualitative methods. The instruments of this research are observation and interviews. The subjects in this study were 3 classrooms of English in intensive class, with 3 teachers and 80 students. Techniques of data analysis are data reduction, data display and drawing conclusion. The results of the study showed that teachers used jigsaw activities, pictures series and group discussions. Discussion groups are a suitable strategy to use when teaching grammar because students can work together with a team. Then by using jigsaw activities can train students' memorization and memory. Moreover, picture series in this way student are trained to be able to express the latest ideas and thoughts so as to increase self-confidence when learning in class, from the three methods used by the teachers, activities in group form more effective because with this method students more enthusiastic in learning.